2008
DOI: 10.1109/toh.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

Physical Collaboration of Human-Human and Human-Robot Teams

Abstract: Abstract-Human partners working on a target acquisition task perform faster than do individuals on the same task, even though the partners consider each other to be an impediment. We recorded the force profile of each partner during the task, revealing an emergent specialization of roles that could only have been negotiated through a haptic channel. With this understanding of human haptic communication, we attempted a "Haptic Turing Test," replicating human behaviors in a robot partner. Human participants cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
168
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(175 citation statements)
references
References 52 publications
2
168
5
Order By: Relevance
“…This work is a preliminary study that investigates the benefits of guidance with collaborative role exchange mechanisms over simple guidance methods. Recent studies on collaborative dyadic interaction displayed the need to define certain roles for the partners [9,13,2]. However, defining the roles for a guidance scheme by examining human-human communication and replicating this interaction by replacing one of the dyads by the computer as a mean of providing guidance proves to be nontrivial especially as the task gets more complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is a preliminary study that investigates the benefits of guidance with collaborative role exchange mechanisms over simple guidance methods. Recent studies on collaborative dyadic interaction displayed the need to define certain roles for the partners [9,13,2]. However, defining the roles for a guidance scheme by examining human-human communication and replicating this interaction by replacing one of the dyads by the computer as a mean of providing guidance proves to be nontrivial especially as the task gets more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Reed and Peshkin [9] examine dyadic interaction to illustrate that partners specialize as accelerators and decelerators within a simple collaborative task. The specialization is said to be subconscious and occurs after several trials but improves performance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a declarative, subjective, evaluation of presence in virtual and remote environments was shown to be unreliable, and behavioral, objective, presence measures, such as postural responses, were suggested (Freeman et al, 2000). In the context of human-robot interaction, (Reed & Peshkin, 2008) showed that while participants who interacted with a robotic partner reported that they interacted with a human in the verbal Turing test, they did not reach the same level of performance as in human-human dyad.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of roles in haptic collaboration is an emerging topic. Reed and Peshkin [13] suggested specialization behaviors such as accelerator and decelerator roles in a target acquisition task. These roles were extracted regarding the interaction of two human operators.…”
Section: Related Workmentioning
confidence: 99%